NEW AMMONOIDS FROM THE SUBFAMILY PROPLANULITINAE BUCKMAN FROM THE UPPER PART OF THE LOWER CALLOVIAN OF CENTRAL RUSSIA - Gulyaev D.B. (My University, 2001)
Two new ammonoid species Proplanulites (Proplanulites) irinae and P. (P.?) rogovi (the most recent known fossils that can be undoubtedly assigned to the subfamily Proplanulitinae) are described from the terminal enodatum Subzone of the Lower Callovian calloviense Zone from the well-known outcrop on the Oka River, near the village of Nikitino. A zonal and subzonal subdivision of the Lower and Middle Callovian beds near the village of Nikitino is proposed.
Keywords: Ammonoid; Proplanulites; Callovian; Jurassic; Oka River; 564.53:551.762.2(470.3); Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Юрская::Средний::Келловейский; Mesozoic::Jurassic::Middle::Callovian